Cationic Complexes of Hydrogen with Helium. Issue 1 (22nd October 2012) - Bartl, Peter; Leidlmair, Christian; Denifl, Stephan; Scheier, Paul; Echt, Olof
Abstract High‐resolution mass spectra of helium nanodroplets doped with hydrogen or deuterium reveal that copious amounts of helium can be bound to H+, H2+, H3+, and larger hydrogen‐cluster ions. All conceivable HenHx+ stoichiometries are identified if their mass is below the limit of ≈120 u set by the resolution of the spectrometer. Anomalies in the ion yields of HenHx+ for x=1, 2, or 3, and n≤30 reveal particularly stable cluster ions. Our results for HenH1+ are consistent with conclusions drawn from previous experimental and theoretical studies which were limited to smaller cluster ions. The HenH3+ series exhibits a pronounced anomaly at n=12 which was outside the reliable range of earlier experiments. Contrary to findings reported for other diatomic dopant molecules, the monomer ion (i.e. H2+) retains helium with much greater efficiency than hydrogen‐cluster ions.